Improving Students’ Achievement and Retention in Biology using Flipped Classroom and Powerpoint Instructional Approaches: Implication for Physics Teaching - Juliet Adonu, Chioma; Rose Nwagbo, Chinwe; Sunday Ugwuanyi, Christian; Okeke, Chinedu I.O. (International Journal of Psychosocial Rehabilitation, 2024)
In Enugu State, Nigeria, the study determined the efficacies of Flipped classroom and PowerPoint instructional approaches on students’ achievement and retention in biology. Anon-equivalent groups quasiexperimental research design was used for the study with a sample size of 79 students. Students’ achievement and retention in Biology were measured using Biology Achievement Test (BAT). Using Kudder-Richardson 20 (K-R20) formula, the internal consistency reliability coefficient of BAT was calculated to be 0.89.Thetest-retest method was used to assess the temporal stability of the reshuffled form of BAT, which was then subjected to Pearson correlation coefficient which yielded a correlation coefficient of 0.91. To answer the research questions, the data were analysed using mean and analysis of covariance (ANCOVA) was used to test the hypotheses at 0.05 level of significance. The study found that both flipped classroom and powerpoint instructional approaches enhanced students’ biology achievement and retention. However, flipped classroom instructional approach was significantly (p< .05) more effective in enhancing biology students’ achievement and retention than powerpoint. Based on the findings of the study, it was recommended that science teachers/science educators should adopt flipped classroom instructional approach for teaching biology and other science subjects like physics